Knowledge management at The National Library of Malaysia / Jamaliah Mohd Nayan - Jamaliah , Mohd Nayan (2005)
The emergence of the new economy that is based on knowledge in the present era has definitely affected everyone and every organization including libraries. Knowledge is seen by most organizations as an overriding and important commodity and if managed properly can assist the organizations to improve their services and remain sustainable and significant in the near future. This study is carried out to assess the organizational working culture of the National Library of Malaysia as to whether it would support the efforts of managing knowledge in the organization. The explorative study using triangulation method consisting of interviews, observations and questionnaire were conducted to investigate the situation. Two hundred questionnaires on knowledge management issues were distributed to the staff of the organization and a total of 72% of it was duly filled and returned. Analysis of the data revealed that most of the respondents that participated in the survey are familiar with the concept of knowledge management and that the National Library has all the required tools and systems to manage knowledge in the organization. However, it was anticipated to come up with a Knowledge Management System whereby persons with specific knowledge and expertise can be located easily and the organization should document the best practices and expertise it requires to successfully conduct the services offered to the library users. Therefore, a conceptual framework called the PNM Knowledge Bank is proposed in the final chapter hopping that it could act as the medium for knowledge capturing and dissemination in the organization.